Comparison of Perioperative, Renal Functional, and Oncological Outcomes Between Off-Clamp and On-Clamp Robot-Assisted Partial Nephrectomy for Renal Tumors: An Updated Evidence-Based Analysis - Huang, Yin; Cao, Dehong; Chen, Zeyu; Chen, Bo; Li, Jin; Guo, Jianbing; Dong, Qiang; Wei, Qiang; Liu, Liangren (Frontiers in Oncology, 2021)
Objectives: To report the latest and largest pooled analysis and evidence update to compare the perioperative, renal functional and oncological outcomes between off-clamp and on-clamp robot-assisted partial nephrectomy (RAPN) for renal tumors. Patients and Methods: We performed a systematic literature search using PubMed, Embase and Web of Science up to August, 2021 for studies that compared the efficacy and/or safety between off-clamp and on-clamp RAPN for renal tumors. Outcomes measured were operating time, estimated blood loss (EBL), conversion rate, length of stay (LOS), complication rate, transfusion rate, long-term % decrease in estimated glomerular filtration rate (eGFR), positive surgical margins rate and recurrence rate. Results: A total of 21 eligible articles involving 4493 patients (1274 off-clamp versus 3219 on-clamp) were included for the evidence synthesis. Baseline characteristics of the two groups were similar in all outcomes except that lower R.E.N.A.L. score and smaller tumor size were observed in the off-clamp group. Pooled analysis showed shorter operative time, higher EBL and lower complication rate in the off-clamp group. No significant difference was observed in the conversion rate, LOS and transfusion rate. The recurrence rates were similar in the two groups, while lower positive surgical margins rate was observed in the off-clamp group. Finally, the off-clamp group had a superior postoperative renal functional outcome. Conclusions: Given the presence of heterogeneity and potential bias, urologists should select the clamp strategy based on their experience and patient-specific factors.